Local de-condensation of double-stranded DNA in oppositely charged polyelectrolyte as induced by spermidine1. Issue 23 (21st June 2015) - Pan, Wei; Zhou, Jihan; Yin, Yudan; Wen, Hao; Liang, Dehai
<x xml:space="preserve">Abstract</x> Polyamines such as spermidine were able to locally transform DNA into a coiled conformation by competing with positively charged polylysine.